The impact of recruitment of materials to improve energy efficiency in buildings - Bin Ali, Rubaia Ali; Gohar, Fahd Saleh; Mukaydekh, Amr Rubaia (Journal of engineering sciences and information technology, 2023)
The issue of saving energy consumption and improving the effectiveness of its use in buildings and facilities is the core of the main subject of the study in this research. Therefore, the goal that the researchers focused on is to learn more about the properties of materials that can be used in the building, and re-motivate them to be employed in a way that improves energy efficiency in the building.There are many materials around us that we do not care about. A grass tossed by waves of the sea, organic matter extracted from petroleum derivatives, or even moss growing in a neglected environment may play an important role in improving energy efficiency. Heating simple materials such as ceramics that have an optimal thermal storage mechanism, or the important crystalline silicon element in the manufacture of solar cells, or by using chemical techniques evaporation method which has a wide range of radiation absorption, all this can significantly raise the energy efficiency of buildings. In designing energy-efficient buildings, it is very important to consider a number of important trends such as: Reducing heat entry or loss through of building components, improve the effectiveness of energy extracted from renewable sources and storage. As well as ensuring efficient energy economy for all functional systems in the building. In most of these areas, those materials are playing the vital role.
Keywords: activating energy efficiency; thermal protection of buildings; thermal insulation materials; vacuum insulation panels